Power analysis for experimental research : - Bausell, R. Barker (Cambridge University Press, 2002)
Power analysis is an essential tool for determining whether a statistically significant result can be expected in a scientific experiment prior to the experiment being performed. This comprehensive, accessible book provides practicing researchers with step-by-step instructions for conducting power/sample size analyses, assuming only basic prior knowledge of summary statistics and normal distribution. It contains a unified approach to statistical power analysis, with numerous easy-to-use tables that make further calculations or statistical expertise unnecessary.